Deficits for the Rich: Inequality and Instability. Issue 2 (2nd April 2020) - Medlen, Craig; Chen, Zelin
Abstract: Deficit spending has long been understood as a stabilizing counter-cyclical force. The thesis presented herein is that over recent decades, the cumulative deficits of government and non-corporate entities have expanded the inequality of wealth and income, which, over the long haul, contributes to slow growth and potential instability. The thesis builds on the Kaleckian-Minsky insight that deficits create gross profits in excess of new investment expenditures (free cash). Since the 1980s, this free cash has been spilled in the stock market through mergers, dividends and stock buybacks—worsening inequality. As the upper classes have a larger range of discretionary spending options, this expanded inequality has made for more spending volatility and speculative endeavors. The authors call for expanded taxes on the rich to claim the deficit-generated free cash. Such taxes would be in the service of more stability and equity.